Respostas

2014-04-13T19:39:31-03:00
A) 3/ V2      => 3 x V2 / V2 x V2  => 3V2 / 2
b) 10/ 3V5   => 10 x V5 / 3V5 x V5  =>  10V5 / 3 x 5  =>  2V5 / 3
c) 3/ 4V2     => 3 x V2 / 4V2 x V2    =>  3V2 / 8

A partir daqui usarei o produto da soma pela diferença de dois termos.
(a+b) (a-b) = a² - b²
d)1/ 2+√3    => 1 (2-V3) / (2+V3) (2-V3)  => 2-V3 / (2)² - (V3)²  => 2-V3
e) 1/ √3-√2  => 1 (V3+V2) / (V3-V2) (V3+V2)  => V3 + V2 / (V3)²-(V2)²  => V3+V2
f) 2-√2/ √2-1 => (2-V2) (V2+1) / (V2-1) (V2+1)  => 2V2+2-2-1 / (V2)²-(1)² => 2V2-1 

Espero ter ajudado ^.^ Qualquer duvida, só chamar
2 5 2